Gelation in free-radical crosslinking copolymerization; fast transient fluorescence study - Ö. Pekcan; D. Kaya (International Journal of Photoenergy)
The fast transient fluorescence (FTRF) technique was used to study the sol-gel phase transition in free-radical crosslinking copolymerization (FCC) in two different monomeric systems. Pyrene (Py) was used as a fluorescence probe for the in situ polymerization experiments. The fluorescence lifetimes of Py from its decay traces were measured and used to monitor the gelation process. Monomer consumption profiles were determined during gelation process using Stern-Volmer model. Gelations were performed at various temperatures and in various crosslinker contents. Composite rate constants, kr were determined and gelation activation energies, ΔEG were measured.